Navigating language barriers: Translingual discrimination and resilience among Indonesian migrant workers in Kuwait - Helena Verusha Ali; Bayu Andika Prasatyo; Yanuarius Yanu Dharmawan (Indonesian Journal of Applied Linguistics)
This study examines the experiences of Indonesian migrant workers (IMWs) in Kuwait, focusing on the discrimination they face due to their multilingual abilities and the strategies they use to overcome this discrimination. Linguistic discrimination continues to significantly influence migrant workers, yet there is a lack of research on their experiences in Middle Eastern contexts. To address the gap, this study aims to explore the perceptions and reactions of individuals from immigrant and minority backgrounds toward linguistic prejudice. Data were gathered from three IMWs (two females and one male, aged 25–40) through semi-structured interviews, using a qualitative research method. The thematic analysis by Braun and Clarke (2019) along with Dryden and Dovchin’s (2021) translingual discrimination model and Dovchin’s (2019) strategies for combating language-based prejudice were employed to analyze the data. The results uncovered three primary manifestations of discrimination: accent-based prejudice, excessive correction, and stereotyping of those who speak 'broken English.' Additionally, those with immigrant-sounding names encountered name-based bias in public spaces such as hospitals. Initially, IMWs utilized nonviolent tactics such as altering their accents and ignoring offensive remarks. Gradually, they embraced more proactive strategies, such as expressing opposition to discriminatory behaviors and reintegrating their original language characteristics. These findings highlight the ability of IMWs to demonstrate resilience in the face of discrimination and emphasize the importance of implementing inclusive language policies to promote fairness in global work environments. This study enhances the understanding of linguistic barriers and prejudice while offering valuable insights into fostering inclusive work settings for migrant workers.